Potensi Benturan Kepentingan Direksi dengan Pemegang Saham dalam Perseroan Perorangan - Perindha Novera, Rahmah (UNES Law Review, 2023)
In order to improve the ease of doing business, one of the measures taken by the government is to provide regulations related to Sole Proprietorship Companies by amending the Law on Limited Liability Companies through the Job Creation Law. The provision divides Limited Liability Companies into capital partnership legal entities and sole proprietorship legal entities. In a sole proprietorship legal entities, there is no clear division of company organs as in a capital partnership legal entity, so that the boundaries of responsibility between directors and shareholders become blurred, it is difficult to determine when the owner acts as a director or shareholder. Meanwhile, directors and shareholders have different authorities and responsibilities. For this reason, it is necessary that the shareholder and director options are different people, so that there is a separation between shareholders and directors. This research uses normative legal research methods by examining primary legal materials in the form of laws and regulations related to individual companies; secondary legal materials in the form of textbooks, legal journals, articles, legal expert opinions; and tertiary legal materials, in the form of news from the mass media.